Effect of wing form on the hydrodynamic characteristics and dynamic stability of an underwater glider - Javaid, M.Y. (Society of Naval Architects of Korea, 2017)
We are developing a prototype underwater glider for subsea payload delivery. The idea is to use a glider to deliver payloads for subsea installations. In this type of application, the hydrodynamic forces and dynamic stability of the glider is of particular importance, as it has implications on the glider's endurance and operation. In this work, the effect of two different wing forms, rectangular and tapered, on the hydrodynamic characteristics and dynamic stability of the glider were investigated, to determine the optimal wing form. To determine the hydrodynamic characteristics, tow tank resistance tests were carried out using a model fitted alternately with a rectangular wing and tapered wing. Steady-state CFD analysis was conducted using the hydrodynamic coefficients obtained from the tests, to obtain the lift, drag and hydrodynamic derivatives at different angular velocities. The results show that the rectangular wing provides larger lift forces but with a reduced stability envelope. Conversely, the tapered wing exhibits lower lift force but improved dynamic stability. © 2016 Society of Naval Architects of Korea